THE USE OF GRAPHIC THINKING ORGANIZER TO TEACH READING OF A REPORT TEXT IN SMAN 1 TANAH GROGOT (RETAIN, 2016)
Abstrak Membacaadalahsalahsatuketerampilanbahasa yang penting. Melaluimembaca, seseorangdapatmeningkatkanpengalaman, mengembangkankonsepbaru, danmemecahkanmasalah-masalahnya. Membacaketerampilan yang diperlukanuntukmemastikanperkembanganpertumbuhanpribadidanuntukmengadopsiperubahan di dunia, namunpentingnyamembacabelumdisadariolehsebagianbesarwarganegara Indonesia. Kebiasaan guru membacabahan ajar yang hanyaberfokuspadapengucapandankosa kata yang tidakmembantusiswauntukmemahamiteksdenganbaik. . Guru harusmembimbingsiswadalam proses membacadalamrangkauntukmembuatmerekalebihmudahuntukmemahamiteks. Salah satucarauntukmembimbingsiswadalam proses membacajugamemotivasimerekadalambelajarbahasaInggrisadalahdenganmenggunakanGraphic Thinking Organizerdalammengajarmembaca, terutamamengajarlaporanmembaca. Graphic Thinking Organizeradalahtampilan visual yang digunakanuntukmengaturinformasi yang diperolehdariteks yang dapatmembantusiswauntukbelajardanmemahamiinformasidenganmudah. Penelitianinimerupakanpenelitiandeskriptifkualitatif. Subyekpenelitianiniadalahsiswakelas XI SMAN 1 Tanah Grogot. Instrumen yang digunakanuntukmendapatkan data yang catatanlapangan, transkrip audio atau video, wawancaragarispanduandanhasiltugasmembacasiswa.Adatigapoin yang bisadilihatdalamhasilpenelitianini. Pertama, pelaksanaanGraphic Thinking Organizersebagaistrategiuntukmengajarmembacalaporanteksberjalandenganbaik. Kedua, siswahasiltugasmembacamenunjukkanbahwasiswakemampuanmembacacukupbaik. Ketiga, siswamenunjukkanresponpositifterhadappelaksanaanGraphic Thinking Organizer. Kesimpulannya, Graphic Thinking Organizerdapatdigunakanuntukmengajarkanmembacalaporanteksuntuksiswakelassebelas. Hal inibergunauntukmembantusiswadalammembacalaporanteks. Keywords: Graphic Thinking Organizer, Membaca,Teks Report, Responsiswa Abstract Reading is one of the important language skills. Through reading, one can enhance his experience, develop new concept, and solve his problems. Reading skill is needed to ensure the development of personal growth and to adopt the change in the world, yet the importance of reading has not been realized by most of Indonesian citizen.The teacher’s habit of teaching reading which only focuses on the pronunciation and the vocabulary does not help students to comprehend the text well. . The teacher should guide the students in the process of reading in order to make them easier to comprehend the text. One of the ways to guide the students in the process of reading also motivate them in learning English is by using graphic thinking organizer in teaching reading, especially teaching reading report. Graphic Thinking Organizer is a visual display used to arrange information gained from a text which can help the students to learn and understands the information effortlessly. This research is a descriptive qualitative research. The subjects of this research are the eleventh graders of SMAN 1 Tanah Grogot. The instruments used to gain the data are field note, audio or video transcript, interview guide lines and students’ reading task result.There are three points that can be seen in the result of this research. First, the implementation of graphic thinking organizer as a strategy to teach reading report text run well. Second, the students’ reading task result showed that the students’ reading ability was good enough. Third, the students showed a positive response toward the implementation of graphic thinking organizer. In conclusion, graphic thinking organizer can be used to teach reading report text for the eleventh graders. It is useful to help the students in reading report text. Keywords: Graphic Thinking Organizer, reading, report text, students’ response